COMPARATIVE ANALYSIS AND HANDYMAN SERVICES APPLICATION DEVELOPMENT - Hafiz Adil Sikandar; Shahbaz Mubashar; Shahan Yamin Siddiqui; Arslan Abbas; Tajammal Hussain Awan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Android Handyman Application provides users with a fast and reliable means to contact the best odd- jobbers around them. In Pakistan, for a domestic job, the selection of blue-collar workers has always been a challenging task. The main focus of this survey is to create our mobile-based android application, where people can contact handymen. A handyman is a term used to describe technicians, including Carpenter, AC Mechanics, Plumbers, Car Mechanic, Electricians, and Painters. The application was developed using Android Studio, code is written using Java and Android SDK, and to store data of oddjobbers, SQLite was used. The research was conducted based on similar work in the form of literature review and related websites. The inspiration behind this was the difficulties one had to face in finding a skilled person to solve his/her household issues. In Pakistan, there is no such Android-based application available to provide ease to smartphone users. As the scope of the android application is concerned, statistics indicate that the trend of surfing the internet on smart devices has seen a steep increase during the past few years. This trend is likely to continue due to a drop in the cost and availability of smart devices. Pakistan, being a developing country has huge potential in the field of the mobile software industry, and the rise in Smartphone usage is most likely to be a perpetual entity. These sorts of uses can increase business open doors for jacks of all trades division which is far deserted from the general public, where mechanical headways are advancing step by step and individuals will in general rely more upon innovation to meet their necessity than any time in recent memory.